Methodology for calculating the fractional content of dust after cleaning in cyclone-type dust collectors and its post-cleaning - V. Yu. Solomin; L. O. Shtripling; Vit. Yu. Solomin (Омский научный вестник, 2025)
The problem with using cyclone dust collectors is the insufficient degree of cleaning of small dusts. Therefore, it is necessary to introduce sequential post-cleaning to meet the requirements of the MAC. Usually, the calculation of the residual dust concentration is carried out on average, which does not give a complete picture of the fractional content of dust after cleaning and increased breakthrough of small fractions. This article presents a method for calculating the fractional residual dust concentration for its sequential post-cleaning using an electrostatic precipitator.